Find the solution to:
9 x − 1 − 3 x − 1 − 2 = 0
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Neat solution :D....
Log in to reply
Thanks. One of my first solutions here and the first one to get some response. :-)
First, we write the equation using a common base for the exponential expressions: ( 3 2 ) x − 1 − 3 x − 1 − 2 = 3 2 x − 2 − 3 x − 1 − 2 = 0 . Thus
3 2 x − 2 − 3 x − 1 − 2 = 3 2 x 3 − 2 − 3 x 3 − 1 − 2 = 9 3 2 x − 3 3 x − 2 = 0
Making the substitution y = 3 x , so y 2 = 3 2 x , we have 9 y 2 − 3 y − 2 = 0 . Multiplying by 9 gives y 2 − 3 y − 1 8 = ( y − 6 ) ( y + 3 ) . Thus 3 x = − 3 , 6 . The first has no real solution, but the second has solution x = l o g 3 6 .
Problem Loading...
Note Loading...
Set Loading...
3 2 ( x − 1 ) − 3 x − 1 = 2
Let y = 3 x − 1
y 2 − y − 2 = 0
So y = 2 , − 1
As y = 3 x − 1 , so y can only be positive i.e. 2 .
So we have -
3 x − 1 = 2
( x − 1 ) lo g 1 0 3 = lo g 1 0 2
( x − 1 ) = lo g 3 2
x = lo g 3 2 + lo g 3 3
x = lo g 3 6